Edukasi Kriminologi Digital melalui Program Sekolah Anti Flexing dan Judi Online bagi Generasi Z - Arka Atyanta; Arif Awaludin; M. Syamsudin (Universitas Wijayakusuma Purwokerto, 2026)
The rapid development of information technology and social media has significantly transformed the social interaction patterns of Generation Z. While digital platforms provide easier access to information and communication, they have also created new criminogenic factors, particularly the growing culture of flexing and online gambling. These phenomena not only produce social and economic consequences but also increase the risk of deviant behavior and technology-based criminal activities among young people. This Community Service Program (PkM) aimed to enhance the legal awareness, digital literacy, and understanding of Generation Z through the Anti-Flexing and Online Gambling School Program, employing Criminology and Cyber Criminology approaches. The program was implemented through legal counseling, digital criminology education, case-based learning, interactive discussions, and consultation sessions addressing current digital issues. The results demonstrated a significant improvement in participants' understanding of digital criminology, criminogenic factors in cyberspace, the dangers of flexing, and the legal, social, psychological, and economic impacts of online gambling. Furthermore, the program successfully strengthened participants' critical thinking skills in evaluating digital content, identifying deviant behavior on social media, and fostering legal awareness in the responsible use of digital technology. The activity also encouraged a collective commitment to promoting a healthy digital culture by rejecting excessive flexing and online gambling practices. Therefore, the Anti-Flexing and Online Gambling School Program can be considered an effective preventive educational model for strengthening legal awareness and digital literacy as part of broader efforts to prevent cybercrime among Generation Z